A comparison of energy vectors in powering hybrid buses. Issue 2 (March 2016) - Charters, Derek
Abstract : HORIBA MIRA's Derek Charters, Senior Consultant – Future Transport Technologies, analyses the different energy vectors used by bus manufacturers and introduces the benefits of utilising liquid nitrogen.